“CORPORATE SOCIAL RESPONSIBILITY (CSR) IN ENGLISH PREMIER LEAGUE: POSITIVE DRIVE IN IMPROVING THE COMMUNITY” - Abu Bakar, Noorherdawaty (2013)
In the field of Corporate Social Responsibility, there have not been many academic literatures on football and its integration with CSR. However, it is quite easy to find various articles and writings about sport and CSR. For this research, it was decided to concentrate on three key issues: to understand the motivations that drive football clubs to implement CSR activities; to describe the benefit it entails to the organisation and to describe as well how the CSR activities affects the community. The research would also consider recommendations for improving practice across the areas of investigation. The research was undertaken by focusing on the key organisation, The Premier League (PL) and all the 20 football clubs for the 2012/2013 season. All data were collected mainly from the main website of PL and the football clubs. Apart from that, information from annual report, CSR and Sustainability report were also referred to in order to provide informational support for this research. The research findings begin by setting out the background of the case study and then the key issues are developed in the results and discussion sections with relevant references. The findings from the research reveal an extending conception of CSR within football mainly by implementing the Community Trust Model, and adding to that, a detailed explanation on the motivations that supposedly influence the organisation on implementing CSR. Diverse community programs are identified and then analysed and lead to further discussion on how the implementation of these activities can deliver benefits for both parties that are the business and the community. The key issues are taken forward into the research’s conclusion, which considers the future direction of the CSR programs of football clubs and recommendations for further research.